Differences in the intrinsic immunogenicity and allergenicity of Bet v 1 and related food allergens revealed by site‐directed mutagenesis. Issue 2 (14th November 2013) - Roulias, A.; Pichler, U.; Hauser, M.; Himly, M.; Hofer, H.; Lackner, P.; Ebner, C.; Briza, P.; Bohle, B.; Egger, M.; Wallner, M.; Ferreira, F.
Abstract Background Birch pollen allergies are frequently associated with adverse reactions to various fruits, nuts, or vegetables, described as pollen–food syndrome (PFS) and caused by cross‐reactive IgE antibodies primarily directed against Bet v 1. Specific immunotherapy (SIT) represents an effective treatment for inhalant allergies; however, successful birch pollen SIT does not correlate well with the amelioration of concomitant food allergies. Methods As vaccine candidates, apple Mal d 1 as well as hazelnut Cor a 1 derivatives were designed by in silico backbone analyses of the respective allergens. The proteins were produced by site‐directed mutagenesis as fold variants of their parental allergens. Because Mal d 1 and Cor a 1 form cysteine‐mediated aggregates, nonaggregative cysteine to serine mutants were also generated. The proteins were characterized physicochemically, immunologically, and in in vivo models with or without adjuvant. Results The structurally modified proteins showed significantly decreased IgE binding capacity. Notably, both in vivo models revealed reduced immunogenicity of the hypoallergenic fold variants. When formulated with alum, the monomeric cysteine mutants induced a similar immune response as the aggregated parental allergens, which is in contrast with data published on Bet v 1. Conclusion These findings lead to the suggestion that the Bet v 1 structure has unique intrinsic properties, which could account for its high allergenicity. Obviously, these characteristics are not entirely shared with its food homologues from apple and hazelnut. Thus, it is important to tackle pollen‐related food allergies from different angles for the generation of effective vaccine candidates to treat birch PFS.